Legitimation and delegitimation of state violence on social media: the case of University of Cauca (2023)
This thesis examines the legitimation and delegitimation of state violence on social media in the case of a student protest at the University of Cauca. To this end, it examines 8421 tweets in order to unravel the specific cultural references and discursive strategies that can be used for legitimizing or delegitimizing the state violence. It conducts qualitative analysis of all tweets by using the general categories of authorization, moral evaluation, rationalization, and dehumanization. Located within the Critical Discourse Studies (CDS), this research especially focuses on the specific mechanisms of delegitimizing social actors, in order to be able to develop discursive strategies that can allow for their re-legitimation. Conceptualizing the 'legitimacy' and 'illegitimacy' of violence as a fluid state instead of a fixed description, this thesis suggests that legitimation and delegitimation of violence are continuous processes, which means that the legitimacy or illegitimacy of a violent act can be changed by making cultural references and using adequate discursive strategies to the context. Since political violence can be legitimized only if other alternatives of conflict resolution or peaceful coexistence are shown to be unlikely, legitimizing political violence usually requires delegitimizing the possible peaceful means of conflict resolution. The four main categories employed in this research and numerous discursive strategies based on them can result in negative other-presentation, which can legitimize exercising violence toward the negatively presented social actors. By examining these strategies, the aim is to find ways that can allow for promoting nonviolence in the Colombian context.